Aroyloxycinnamates with wide mesophase temperature ranges. Issue 6 (3rd May 2022) - Muhammad, Khushi; Riaz, Sharon; Vieira, André A.; de Jesus, Eunice C.; Gonçalves, Itamar; Merlo, Aloir A.; Bechtold, Ivan H.; Hameed, Shahid
ABSTRACT: A new series of eight asymmetric homologues was designed and synthesised by the reaction of aroyloxybenzaldehydes with Wittig salt of methyl bromoacetate, where the length of the alkoxy chain was varied. All the compounds were found thermally stable up to 220°C. Differential scanning calorimetry, polarising optical microscopy and X-ray diffraction were used to study the mesomorphic properties, where a mesophase range of up to 80°C was obtained. The two shorter homologues with C3 –C4 were nematic, the intermediate lengths were nematic and smectic A (SmA) with a progressive increase of the SmA domains and the longest homologue with C12 was purely SmA. The translational order parameter of the SmA mesophases showed that the molecular order inside the smectic layers increases with molecular length, associated with the higher stabilisation and predominance of the SmA phase. All compounds dispersed in solution absorb light in the ultraviolet region. Abstract : uf0001